Dynamic Feedback Flow Control Algorithms for Unicast and Multicast Available Bit Rate Service in Asynchronous Transfer Mode Networks - Abdelrahman, Ali Mohamed (2000)
Asynchronous transfer mode (ATM) network technology has been adopted to integrate different kinds of traffic, like video, audio and data. It provides several service categories including constant bit rate (CBR), variable bit rate (VBR), available bit rate (ABR), and unspecified bit rate (UBR) service. In particular, the ABR service has been approved to use the bandwidth left by CBR and VBR services, which is ideal for data applications and can perform well for real-time applications with the appropriate implementation. Basically ABR servIce attempts to guarantee minimum cell rate, achieve fairness, and minimise cell loss by periodically indicating to sources the rate at which to send. Therefore, there is a critical need for an effective flow control mechanism to allocate network resources (buffers, bandwidth), and provide the negotiated quality of service. This thesis develops dynamic feedback flow control schemes in ATM networks, with primary focus on point-to-point (unicast) and point-tomUltipoint (multicast) ABR algorithms. Firstly, it surveys a number of point-to-point schemes proposed for supporting unicast ABR service. Some of these algorithms do not measure the actual ABR traffic load which leads to either overestimates or underestimates of the bandwidth allocation. Others do not monitor the activity of the sources and overlook the temporarily idle sources. The rest may be implemented with additional complexity. Secondly, the research shifts to the problems of point-to-multipoint algorithms by introducing the basic concept of multicasting ABR servIce and reviewing a group of consolidation schemes, where the compromise between low consolidation nOlse and fast transient response is the main issue. Thirdly, the design and implementation issues have been addressed together with the major drawbacks of the previous schemes and hence two algorithms have been proposed. A dynamic rate-based flow control (DRFC) scheme has been developed to support ABR service in unicast environment, while an adaptive feedback consolidation (AFC) algorithm has been designed for ABR multicasting. Finally, these schemes are extensively tested and compared with others from the literature using a wide range of network configurations and different types of traffic sources. The simulation results show that the DRFC algorithm allocates the available bandwidth fairly among the contending ABR sources, while achieving high link utilisation with reasonable growth of queues. The AFC scheme eliminates the consolidation noise with fast transient response as well as minimising the effect of non-responsive branches.